A study of NTU undergraduates engaging in online discussions versus face to face discussions. - Ng, Li Li. (2008)
The purpose of this report is to investigate how NTU undergraduates response differently in online discussions versus face to face discussions. The report examines how personality, gender and medium of communication can affect group discussions.